Etnografia no movimento: território, hierarquia e lei no PCC - Biondi, Karina (2014)
The First Command of the Capital (PCC), approached here as a Movement, appeared in São Paulo s prisons in the early 1990s and today is present in the majority of penal institutions and urban areas within the State of São Paulo. This approach taken here has two important implications for the thesis. Firstly, it demands reflection on an ethnography in motion. Secondly, instead of conduce to the exposure of forms, it required to make the description of the PCC-making. Thus, this thesis concerns the modes of doing PCC and ethnography. Methods therefore. The seemingly abstract notions that gave name to the parts of this thesis (motion, idea and situation), associated with others that were called to make the descriptions, they all show a (mobile) way of existing and seeing this existence which can be called PCC. Inspired by this practice of knowledge, this thesis presents the description (1) of the movement, composed of countless movements that, refusing spatial demarcations, lead to a critique of the notion of territory; (2) of the ideas, which, without defined origin and predictable or definitive end, bring into question the ways in which the concept of hierarchy are worked in the social sciences; (3) of the situations, which displace the notion of law to not legalistic bases. In short, this thesis presents some characteristics of PCC that allow to replace some key concepts to anthropology. These displacements give the title to this thesis: before naming what will be described, this title indicates what will be challenged by my description about the PCC.